2007
DOI: 10.1177/1090198106290398
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Beliefs About Body Size, Weight, and Weight Loss Among Obese African American Women: A Qualitative Inquiry

Abstract: The purpose of this qualitative study was to explore perceptions and beliefs about body size, weight, and weight loss among obese African American women in order to form a design of weight loss intervention with this target population. Six focus groups were conducted at a community health clinic. Participants were predominantly middle-aged with a mean Body Mass Index of 40.3 +/- 9.2 kg/m(2). Findings suggest that participants (a) believe that people can be attractive and healthy at larger sizes; (b) still feel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
79
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 38 publications
13
79
2
2
Order By: Relevance
“…As shown in previous studies, differences in weight development between men and women could be attributable to hormonal differences, since women need to store energy to ensure their nutrient supply during pregnancy and breastfeeding [30]. In addition, earlier studies propose pregnancy as a reason for obesity [31,32], referring to the difficulty of reversing weight gain after a pregnancy [32]. In a study by Linné et al [32], however, no statistically significant difference could be seen between the women who were overweight and those who had a normal weight in relation to the number of pregnancies or total number of births.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in previous studies, differences in weight development between men and women could be attributable to hormonal differences, since women need to store energy to ensure their nutrient supply during pregnancy and breastfeeding [30]. In addition, earlier studies propose pregnancy as a reason for obesity [31,32], referring to the difficulty of reversing weight gain after a pregnancy [32]. In a study by Linné et al [32], however, no statistically significant difference could be seen between the women who were overweight and those who had a normal weight in relation to the number of pregnancies or total number of births.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has long been thought that members of the African American community were protected against unhealthy weight-related behaviors given their acceptance of a larger body size (Flynn & Fitzgibbon, 1998), recent evidence suggests African American women may also experience weight concern (Befort, Thomas, Daley, Rhode, & Ahluwalia, 2006;Johnsen et al, 2002), body dissatisfaction, unhealthy weight loss behaviors, and eating disorders (Gilbert & Warburton, 2003). This recent data may suggest that postcessation weight gain may be a concern and could be a potential barrier to smoking cessation (Pomerleau, Zucker, & Stewart, 2001;Sánchez-Johnsen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This distribution gives an idea about the perception of obesity based on the geographic location and on the social awareness in the spread of this epidemic. The diagram in Figure 4 (top) classes the factors of obesity into three categories [20]: the first describes environmental determinants, including social and physical factors; the second includes psychological and behavioral factors; and the third consists of biological factors [22], notably the genetic background of the concerned individual [23][24][25][26][27]. A summary diagram ( Figure 5) is carried out on the basis of [20] to illustrate the successive stages of the extraction of 106 studies selecting many factors on three important levels, namely: (i) environmental; (ii) psychological and behavioral; and (iii) biological.…”
Section: A Systematic Reviewmentioning
confidence: 99%
“…Women are more frequently overestimating (respectively underestimating) their weight if their sisters did the same, but more rarely if their brothers overestimate (respectively underestimate) their own weight [7]. In [23], the perception and beliefs about body size, weight and weight loss have been studied in Afro-American obese women. The authors have found that these women believe people are more attractive and healthy at larger sizes.…”
Section: Psychological and Behavioral Factorsmentioning
confidence: 99%